National security system of the Republic оf Kazakhstan: theoretical concept and practice of its implementation (Journal of actual problems of jurisprudence, 2021)
The research is devoted to the organizational structure and functioning of the national security system of the Republic of Kazakhstan, which is evaluated from the perspective of relevant scientific ideas in domestic and foreign science. In the future, this concept is extrapolated to legislative norms in order to determine its full and consistent practical implementation. The study results in the conclusion that to improve the effectiveness of the application of legislative norms, it is necessary to develop specific requirements for ensuring national security, used in strategic planning of directions and stages of socio-economic development of the Republic of Kazakhstan. To solve this problem, the necessary mechanisms are proposed and justified. This issue covers a wide range of issues, among which the Central place is occupied by the conceptual framework for building a national security system, as well as the key parameters for their implementation. In this context, the present study is based on the assessment of compliance of the theoretical model of the national security system of the Republic of Kazakhstan with modern scientific concepts, as well as determining the completeness and completeness of their implementation in the practical activities of the state apparatus. Ensuring national security is based on scientific knowledge, the truth criteria are established by society. Key words: national security, system of ensuring national security, subjects of ensuring national security, national security measures, State planning system.